Effects of exogenous taurine supplementation on the growth, antioxidant capacity, intestine immunity, and resistance against Streptococcus agalactiae in juvenile golden pompano (Trachinotus ovatus) fed with a low-fishmeal diet - Liu, Jia-Xing; Guo, Hua-Yang; Zhu, Ke-Cheng; Liu, Bao-Suo; Zhang, Nan; Zhang, Dian-Chang (Frontiers in Immunology, 2022)
Taurine has various biological functions in fish, playing an essential role in growth, resistance to oxidative stress, and intestine immunity. Here, we evaluated the effects of exogenous taurine added to low-fishmeal diets on the growth, anti-oxidative stress, intestine immunity, and Streptococcus agalactiae resistance in juvenile golden pompano (Trachinotus ovatus). Our study showed that exogenous taurine supplementation of 1.2% (T3 group) greatly enhanced the weight gain rate and specific growth rate (SGR) of juvenile golden pompano, significantly upregulating growth-related factor expression in the brain and liver, as well as the levels of growth-related parameters in the serum. Polynomial regression analysis using SGR estimated the optimal dietary taurine level for golden pompano at 1.18%. Moderate exogenous taurine also increased the muscular thickness and villus length within the intestine, maintained intestinal physical barrier stability, activated the Nrf2/Keap-1/HO-1 signaling pathway, increased intestinal antioxidant enzyme gene expression and antioxidant enzyme activity in the serum, and upregulated immunoglobulin and complement levels in parallel with declining reactive oxygen species (ROS) levels in the serum. Antioxidant factor expression was also upregulated in the intestine. Furthermore, supplementation suppressed NF-κB signaling and intestinal pro-inflammatory cytokine gene expression, increased anti-inflammatory cytokine gene expression, and improved intestine immunity. Finally, taurine supplementation improved the survival rate of golden pompano challenged with S. agalactiae. Overall, our findings provide additional information and support for the rational use of taurine in healthy aquatic animal farming.